INDICATORS OF OPEN SPACE QUALITY FOR CHILDREN IN HIGH- DENSITY SETTLEMENTS - Kusumo Dewi, Diah Intan; Rakhmatulloh, Anita Ratnasari; Amadea, Diva (PLANNING MALAYSIA, 2020)
Open spaces are essential for city sustainability because they offer various functions. One of the benefits of open spaces is their use as outdoor space for physical activities or as learning areas for children. The purpose of this paper is to identify the indicators to measure and define open spaces appropriate for children in urban high-density settlements. This study was conducted in the periurban area of Tembalang, Semarang, Indonesia. In order to determine appropriate indicators, this study made use of environmental characteristics as indicators. The result showed that security, safety, comfort, and accessibility were essential factors of appropriate open spaces for children in urban high-density settlements. The contribution of this paper is to promote the importance of open space for children’s activities.